Emergency contracting and the delivery of elective care services across the English National Health Service and independent sector during COVID-19: a descriptive analysis - Rocco Friebel; Michael Anderson; Laia Maynou; Jon Fistein (BMJ Open)
Background Following a virtual standstill in the delivery of elective procedures in England, a national block contract between the NHS and the independent sector aimed to help restart surgical care. This study aims to describe subsequent changes in trends in elective care service delivery following implementation of the initial iteration of this contract.Methods Population-based retrospective cohort study, assessing the delivery of all publicly funded and privately funded elective care delivered in England between 1 April 2020 and 31 July 2020 compared with the same period in 2019. Discharge data from the Hospital Episode Statistics and private healthcare data from the Private Health Information Network was stratified by specialty, procedure, length of stay and patient complexity in terms of age and Charlson Comorbidity Index.Results COVID-19 significantly reduced publicly funded elective care activity, though changes were more pronounced in the independent sector (−65.1%) compared with the NHS (−52.7%), whereas reductions in privately funded elective care activity were similar in both independent sector hospitals (−74.2%) and NHS hospitals (−72.9%). Patient complexity increased in the independent sector compared with the previous year, with mixed findings in NHS hospitals. Most specialties, irrespective of sector or funding mechanisms, experienced a reduction in hospital admissions. However, some specialities, including medical oncology, clinical oncology, clinical haematology and cardiology, experienced an increase in publicly-funded elective care activity in the independent sector.Conclusion Elective care delivered by the independent sector remained significantly below historic levels, although this overlooks significant variation between regions and specialities. There may be opportunities to learn from regions which achieved more significant increases in publicly funded elective care in independent sector providers as a strategy to address the growing backlog of elective care.